Redesign Tata Letak Fasilitas Produksi Gear Sebagai Upaya Pengendalian Over Transportation - Inggit Novita Putri; Renanda Nia Rachmadita; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
PT. Apie Indo Karunia is one of the companies engaged in the foundry located in Sidoarjo. The company itself is a company that works by order / orderan from the consumer (Make to Order). Some of the products produced are gears, industrial machinery parts, and other steel construction. Products that have serrations are used as research material because of the high level of product order quantity. In this case the problem is the existence of flow back and forth process, so that the emergence of overtrasnsportation that can increase the cost of material handling and also affect the waste of time just for the process of removal. The cause of this alternating flow is because the layout of the machines is irregular (not in accordance with the process of making the gear and does not consider the type of production process of the company in the type of jobshop), where the engine layout should be grouped according to function. In addition, from the irregular arrangement of machines causes a pile of material / product (no special space for products that are queued up or processed). To handle the problem, used Methodatic System Layout Planning (SLP) developed by Richard Muther. The first step is to input data, then make Flow Process Chart, distance, time and speed of material transportation, make Activity Relationship Chart, and Activity Relationship Diagram. Result of research of layout design result 3 layout alternative then chosen one layout proposal selected with nlai cost and distance of best move with total distance material handling 5117,17 m / month and material handling cost every month equal to Rp 1.479.724,- So it can increase the efficiency of material handling cost (OMH) by 54%.